Are recent statin recommendations to employ fixed doses and abandon targets effective for treatment of hypercholesterolaemia? Investigation based on number needed to treat. (29th August 2020) - Soran, Handrean; Adam, Safwaan; Durrington, Paul N
Abstract: Background: Assessed by number needed to treat (NNT) to prevent one event, it was previously shown that for those at similar atherosclerotic cardiovascular disease (CVD) risk, the benefit accruing from treating people with higher cholesterol levels with statins is greater than for those with lower levels. Method: By estimating NNT from both the absolute atherosclerotic cardiovascular risk and the pre-treatment low density lipoprotein cholesterol (LDL-C) concentration, recent recommendations for fixed dose high and moderate intensity statin treatment in the primary and secondary prevention of CVD were compared with cholesterol-lowering therapy aimed at a target LDL-C. Results: We report that the USA and UK recommendations to employ a fixed dose of atorvastatin 20 mg daily for primary prevention will produce good results in people with low cholesterol levels, but are a disadvantage for those with higher levels who benefit more from a therapeutic target and statin dose titration and, where necessary, adjunctive cholesterol-lowering therapy to achieve this target. The higher dose of atorvastatin 80 mg daily with no target recommended for secondary prevention is generally more effective than aiming for a LDL-C goal except in people with particularly high cholesterol. Conclusion: For optimum clinical effectiveness, initial LDL-C concentration must be considered in deciding whether a target will allow a greater decrease in LDL-C and thus a lower NNT than a fixed dose regimen. Individual variation in the LDL-C response to statins also makes post-treatment cholesterol measurement essential.